2016
DOI: 10.1101/gad.276428.115
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of autophagy-dependent and -independent functions of FIP200 revealed by generation and analysis of a mutant knock-in mouse model

Abstract: Autophagy is an evolutionarily conserved cellular process controlled through a set of essential autophagy genes (Atgs). However, there is increasing evidence that most, if not all, Atgs also possess functions independent of their requirement in canonical autophagy, making it difficult to distinguish the contributions of autophagy-dependent or -independent functions of a particular Atg to various biological processes. To distinguish these functions for FIP200 (FAK family-interacting protein of 200 kDa), an Atg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 55 publications
4
74
1
Order By: Relevance
“…Genetically engineered mouse models of lung cancer, pancreatic cancer, and melanoma, driven by either mutant rat sarcoma ( RAS ) or B‐Raf proto‐oncogene, serine/threonine kinase ( BRAF ) in which autophagy genes were deleted, have demonstrated that autophagy suppresses the growth of benign tumors but accelerates the growth of advanced cancers . This also was observed in a mouse model of breast cancer …”
Section: The Dichotomous Role Of Autophagy In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Genetically engineered mouse models of lung cancer, pancreatic cancer, and melanoma, driven by either mutant rat sarcoma ( RAS ) or B‐Raf proto‐oncogene, serine/threonine kinase ( BRAF ) in which autophagy genes were deleted, have demonstrated that autophagy suppresses the growth of benign tumors but accelerates the growth of advanced cancers . This also was observed in a mouse model of breast cancer …”
Section: The Dichotomous Role Of Autophagy In Cancermentioning
confidence: 99%
“…[30][31][32][33][34] This also was observed in a mouse model of breast cancer. 35,36 Mouse models of tumorigenesis should not be used to understand the utility of inhibiting autophagy in the therapeutic context, because autophagy genes are usually deleted in utero at the same time that oncogenes and tumor-suppressor genes are altered. In patients, autophagy inhibitors will be deployed after the cancer is already formed in the adult, and likely in combination with other agents.…”
Section: The Dichotomous Role Of Autophagy In Cancermentioning
confidence: 99%
“…Numerous factors affecting FIP200 levels and post-translational modification likely play into which functions of FIP200 are dominant or indeed exclusive in any given cell type or cellular stress condition. Recent studies have begun to separate out the functions of FIP200 in autophagy from those in other cellular processes (109). By mutating amino acids 582–585 to alanine (FIP200-4A) and preventing the interaction of FIP200 with Atg13 (Autophagy related gene 13), Chen et al were able to block the function of FIP200 in autophagy (109).…”
Section: Autophagy and Cell Motilitymentioning
confidence: 99%
“…Recent studies have begun to separate out the functions of FIP200 in autophagy from those in other cellular processes (109). By mutating amino acids 582–585 to alanine (FIP200-4A) and preventing the interaction of FIP200 with Atg13 (Autophagy related gene 13), Chen et al were able to block the function of FIP200 in autophagy (109). Interestingly, knock-in of the FIP200-4A mutant allele into mice extended the lifespan of Fip200−/− mice from E16.5 (110) to birth when other Atg gene knockout mice are known to die (111).…”
Section: Autophagy and Cell Motilitymentioning
confidence: 99%
“…A requirement for autophagy to maintain tumors in vivo has also been demonstrated for cancers driven by PTEN loss (Santanam et al, 2016). Moreover, additional autophagy regulators such as FIP200, have been shown to maintain tumor growth due to autophagy and not other functions of the protein (Chen et al, 2016). One caveat for many of the mouse studies is that deletion of the Atg gene occurs simultaneously with activation of the oncogenic driver and occurs only in the tumor cells.…”
Section: Targeting Autophagy In Cancermentioning
confidence: 99%